Globalization for Development : Trade, Finance, Aid, Migration, and Policy, Revised Edition - Goldin, Ian; Reinert, Kenneth (Washington, DC : World Bank and Palgrave Macmillan, 2012)
Globalization has been taking place for centuries, moving from the colonization of the inhabited parts of the world to the appearance of nations, from conquests to independent countries, from sailboats and caravans to steamboats, truck fleets and cargo planes, from trade in a few commodities to global production and distribution networks and to the present explosion of international flows of services, capital, and information. This book also helps to shatter a false dichotomy that holds that policies that favor the poor cannot be pro-market. There is an enormous set of pro-poor and pro-market policies that allow for more equal market competition among and within countries, and that ask that policy take account of externalities as much as possible. The sheer size of today's global economy is a testament to the speed of change: in 2005, world economic output total US$35 trillion an amount likely to double by 2030, assuming modest continued growth. In this book the authors provide a comprehensive introduction to key aspects of globalization trade, finance, aid, and migration, and their complex linkages with poverty and development. This book also helps to shatter a false dichotomy that holds that policies that favor the poor cannot be pro-market. There is an enormous set of pro-poor and pro-market policies that allow for more equal market competition among and within countries, and that ask that policy take account of externalities as much as possible.